ZVT high step‐up DC/DC converter with a novel passive snubber cell. Issue 5 (23rd February 2017) - Zhu, Binxin; Ren, Lulu; Wu, Xi; Song, Kun
Abstract : A zero voltage turn‐off high step‐up DC/DC converter is presented. The conversion efficiency and power density are improved significantly by using a novel passive snubber cell, which only consists of two diodes and a snubber capacitor. The converter also provides high‐voltage conversion ratio as well as low‐voltage stress on switches and diodes, which make it suitable for some special industrial applications as electric‐vehicle, uninterruptible power supply system or photovoltaic power generation system. The topology, operation principles and performance characteristics are analysed in detail. Moreover, a maximum 800 W experimental prototype has been developed to validate the effectiveness of the theoretical analysis, and 96.2% efficiency has been achieved.